Clinical outcomes of patients with symptomatic acetabular rim fractures after arthroscopic FAI treatment. Issue 1 (10th October 2017) - Giordano, Brian D; Suarez-Ahedo, Carlos; Gui, Chengcheng; Darwish, Nader; Lodhia, Parth; Domb, Benjamin G
ABSTRACT: This study aims to investigate the influence of the acetabular rim fractures on outcomes of hip arthroscopy at minimum 2-year follow-up. Between January 2009 and August 2012, data were prospectively collected on all patients undergoing hip arthroscopy. Anatomic findings, including presence of rim fractures, were recorded intraoperatively. Patients were assessed preoperatively and at 3 months, 1 year and minimum 2 years postoperatively with four patient-reported outcome measures: modified Harris Hip Score, Non-Arthritic Hip Score, Hip Outcome Score-Activities of Daily Living and Hip Outcome Score-Sport Specific Subscales. Pain was estimated using a visual analog scale. Satisfaction was measured on a scale from 0 to 10. Patients with rim fractures were identified and retrospectively matched to a control group based on gender, BMI category, and age at surgery within 3 years and compared in terms of demographic factors, intraoperative findings, procedures and outcomes. Twenty-one patients with rim fractures were matched to a control group of 21 patients with symptomatic femoroacetabular impingement without rim fractures. No significant differences were detected with respect to demographic characteristics, surgical procedures (besides the removal of rim fractures), or in terms of preoperative, postoperative, or improvement in patient-reported outcome scores and satisfaction. The presence or absence of an acetabular rim fracture does not significantly influence clinical outcomes at minimum 2-year follow-up after hip arthroscopy. Case–control study design is used in this study.